Multicenter evaluation of single-photon emission computed tomography quantification with third-party reconstruction software. Issue 9 (September 2016) - Kangasmaa, Tuija S.; Constable, Chris; Hippeläinen, Eero; Sohlberg, Antti O.
Abstract : Reliable and reproducible quantification is essential in many clinical situations. Previously, single-photon emission computed tomography (SPECT) has not been considered a quantitative imaging modality, but recent advances in reconstruction algorithm development have made SPECT quantitative. In this study, we investigate the reproducibility of SPECT quantification with phantoms in a multicenter setting using novel third-party reconstruction software. A total of five hospitals and eight scanners (three GE scanners and five Siemens scanners) participated in the study. A Jaszczak phantom without inserts was used to calculate counts to activity concentration conversion factors. The quantitative accuracy was tested using the NEMA-IEC phantom with six spherical inserts (diameters from 10 to 37 mm) filled to an 8 : 1 insert-background concentration ratio. Phantom studies were reconstructed at one central location using HERMES HybridRecon applying corrections for attenuation, collimator-detector response, and scatter. Spherical volumes of interest with the same diameter as the inserts were drawn on the images and recovery coefficients for the spheres were calculated. The coefficient of variation (CoV) of the NEMA-IEC phantom recovery coefficients ranged from ∼19 to 5% depending on the insert diameter so that the lowest CoV was obtained with the largest spheres. The intersite CoV was almost equal to intrasite CoV. In conclusion, quantitative SPECT is reproducible in a multicenter setting with third-party reconstruction software.